2008
DOI: 10.1111/j.1442-2042.2008.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Loxoprofen sodium treatment for elderly men with refractory nocturia: Effect on night‐time urine production

Abstract: Abstract:We evaluated the efficacy of loxoprofen sodium for refractory nocturia. Twelve men (mean age, 75.1 Ϯ 5.7) with nocturia were enrolled in this study. All patients received 60 mg loxoprofen sodium prior to sleeping at night for 14 days. Nine of 12 patients (75%) felt more satisfaction than previous treatments. Patients were grouped into a loxoprofen sodium-effective (n = 7) and ineffective groups (n = 5) based on the results of the frequency-volume chart. In the effective group, interestingly, night-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Several other treatment approaches have been explored in various populations with nocturia, but none of them has been systematically tested. Nocturia related to nocturnal polyuria has been reported to be sensitive to treatment with the cyclooxygenase inhibitors such as diclofenac 112 or loxoprofen 113 . Within the group of OAB patients, the serotonin‐norepinephrine uptake inhibitor duloxetine has also been reported to improve nocturia 114 .…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other treatment approaches have been explored in various populations with nocturia, but none of them has been systematically tested. Nocturia related to nocturnal polyuria has been reported to be sensitive to treatment with the cyclooxygenase inhibitors such as diclofenac 112 or loxoprofen 113 . Within the group of OAB patients, the serotonin‐norepinephrine uptake inhibitor duloxetine has also been reported to improve nocturia 114 .…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Nocturia related to nocturnal polyuria has been reported to be sensitive to treatment with the cyclooxygenase inhibitors such as diclofenac 112 or loxoprofen. 113 Within the group of OAB patients, the serotonin-norepinephrine uptake inhibitor duloxetine has also been reported to improve nocturia. 114 At least among men with LUTS/BPH surgical treatment has also been reported to improve nocturia.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The effectiveness of hypnotic or non-steroidal anti-inflammatory drugs has been reported; however, such drugs have positional side effects including affinity for benzodiazepine which is associated with adverse effects on cognitive function with the potential for abuse, dyspepsia, and nephropathy. For ramelteon on the other hand, both safety with chronic insomnia have been reported in Japanese patients [12,13,27]. Therefore, we selected ramelteon for the BPH patients with nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of loxoprofen and nocturia, Okada et al reported that nocturia was reduced by approximately 1.6 times when loxoprofen was taken before sleep for 2 weeks [8]. Saito et al had patients take loxoprofen before sleep for 1 week and reported the improvement of nocturia by approximately two times [9].…”
Section: Discussionmentioning
confidence: 99%